RPL41 inhibits the proliferation and migration of retinoblastoma through the ARL5B-associated lysosomal trafficking - Li, Ye; Zhan, Tian; Chen, Tianfu; Zhong, Qianwen; Xiao, Sheng; Wang, Aiyuan; Jiao, Yisheng (Frontiers in Immunology, 2025)
PurposeRetinoblastoma is the most common intraocular cancer in infants and children, with a significant potential for metastasis. The mini-peptide ribosomal protein L41 (RPL41) has demonstrated extensive antitumor effects in vitro by promoting the degradation of activating transcription factor 4 (ATF4). This study aims to evaluate the therapeutic effect of RPL41 on retinoblastoma and elucidate its potential mechanisms.MethodsA xenografted retinoblastoma model was constructed in nude mice. The effects of xenografted RPL41 on tumor proliferation, invasion and metastasis were evaluated by local injection. Mass spectrometry identified differentially expressed genes in Y79 and Weri-RB1 retinoblastoma cells pre- and post-treatment. We utilized quantitative real-time PCR (qRT-PCR), Western blotting, and immunohistochemistry to assess the expression levels of ARL5B(ADP ribosylation factor like GTPase 5B) in retinoblastoma cell lines and tissues. We also explored ATF4’s regulatory role on ARL5B expression through chromatin immunoprecipitation (ChIP) experiments and luciferase reporter gene assays.ResultsRPL41 inhibits the growth of subcutaneous retinoblastoma xenografts. ARL5B expression was significantly downregulated in treated Y79 and Weri-RB1 cells. ARL5B was upregulated in retinoblastoma cells and clinicopathological tissues. RPL41 treatment led to ATF4 degradation, reducing the expression levels of ARL5B and lysotransfer-related molecules. Knocking down ATF4 decreased ARL5B protein levels. ChIP experiments and dual-luciferase assays confirmed ATF4 positively regulates ARL5B. Rescue experiments indicated that ARL5B overexpression partially reversed the effects of RPL41 therapy or ATF4 knockdown on lysosomal pathways and cell migration.ConclusionsRPL41 down-regulates the expression of ARL5B by degrading ATF4 and the impaired ARL5B-related lysosomal trafficking is a mechanism to inhibit the metastasis of retinoblastoma.